Accessibility of welfare facilities for elderly people in Daejeon, South Korea considering public transportation accessibility. (December 2021) - Cho, Hyemin; Choi, Junyong; No, Wonjun; Oh, Minseok; Kim, Youngchul
Highlights: Investigated accessibility to welfare facilities for elderly people. Identified the spatial inequity of facilities for elderly people. Illustrated spatial inequity of elderly's welfare facilities in Daejeon, South Korea. Improving public transport would increase spatial equity of welfare facilities. Abstract: With the spread of an aging society, the mobility constrained seniors' need for public transportation is increasing. This paper investigates accessibility to welfare facilities for elderly people, that is, whether elderly people can easily access the welfare facilities that they frequently visit. We consider welfare facilities including residential welfare institutions, medical and welfare institutions, leisure and welfare institutions, and commuting-system welfare facilities. We verify spatial distribution of welfare facilities and relationship to the unequal development of urban or public transportation networks. Inequality of accessibility was found between the urban and suburban areas of the study area. This paper identified the spatial inequity of facilities for elderly people by measuring spatial accessibility considering public transportation accessibility and walking time to the facilities. This paper suggested that improving public transportation accessibility would increase the spatial equity of welfare services for elderly people.